Remediation of phenanthrene contaminated soil through persulfate oxidation coupled microbial fortification. Issue 5 (October 2021) - Li, Dan; Zhao, Yaqin; Wang, Liping; Wei, Shaohua; Huang, Shaomeng
Abstract: The technology of chemical oxidation coupled microbial remediation of polycyclic aromatic hydrocarbons contaminated soil was efficient and friendly, but the research on the compatibility of chemical oxidation and the bioremediation is insufficient. This study was to explore the compatibility of persulfate oxidation coupled microbial degradation and promote the remediation of phenanthrene contaminated soil. The results showed that the addition of persulfate with the participation of Fe 2+ caused the soil environment to be acidic and the soil pH with the lower concentrations (20, 50 mmol/L) of persulfate returned to neutral after 14 days. The content of fulvic-like and humic-like increased after adding persulfate at the same time. Persulfate inhibited the activity of soil dehydrogenase and polyphenol oxidase, simultaneously, the oxidation species generated during the persulfate oxidation process and the acidic environment (pH=4.13) led the soil microbial abundance and diversity to decrease significantly. Besides, the phenanthrene degradation bacterial consortium was screened through a gradual domestication process, which derived from activated sludge in the coking plant wastewater aeration tank of Xuzhou Weitian Chemical Co., Ltd. The efficient degrading bacteria were identified as Pantoea (95%) using high-throughput sequencing, with the 84% degradation rate of phenanthrene after the 7th day. Comparing persulfate oxidation, the removal rate of phenanthrene in the soil was increased by 33% after 63 days of the combined remediation. Adding 20 mmol/L persulfate and inoculating domesticated high-efficiency degrading bacteria Pantoea was recommended in the remediation of PAHs contaminated soil. Graphical Abstract: ga1 Highlights: Soil environment and indigenous microorganisms under persulfate oxidation were observed. The domesticated degrading bacteria are mainly Pantoea (95%). 20 mmol/L persulfate coupled Pantoea was recommended to remediate PAHs contaminated soil.